Guidelines for evaluation of investment in information technology (REGE Revista de Gestão, 2007)
The impact of information technology, IT, investment on business was discussed from economic and management standpoints in an evaluation based upon a review of literature and empirical and technical management surveys. Factors and techniques used as a means by those responsible for organizational IT investments were identified as guidelines for decisions to maximize possibilities for management of sustainable competitive advantages. Finally, future research lines for evaluation of IT investments were also identified.